2021
DOI: 10.1002/ece3.7643
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota are associated with sex and age of host: Evidence from semi‐provisioned rhesus macaques in southwest Guangxi, China

Abstract: et al., 2020). Numerous studies have focused on the effect of diet on gut microbiota. These studies indicate that diet can rapidly alter the composition of a host's gut microbiota (David et al., 2014;De Filippo et al., 2010). Different diets provide a variety of nutritional substrates to the intestinal microbiota, allowing its growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 63 publications
(117 reference statements)
2
15
0
Order By: Relevance
“… 117 Sequencing analysis of rhesus macaques ( Macaca mulatta ) fecal samples revealed that female macaques had higher levels of alpha diversity and a more distinctive microbial structure than males, and those mature individuals had a higher abundance of Oscillospira compared to immature individuals. 75 Similarly, the abundance of Oscillospira in male and female ASD rodent models exhibited substantial differences, and these differences may be due to sex specificity. 71 , 72 Xi et al found that the abundance of Oscillospira in the gut of specific-pathogen-free chickens decreased with increasing age.…”
Section: Factors Affecting the Abundance Of Oscillospiramentioning
confidence: 99%
“… 117 Sequencing analysis of rhesus macaques ( Macaca mulatta ) fecal samples revealed that female macaques had higher levels of alpha diversity and a more distinctive microbial structure than males, and those mature individuals had a higher abundance of Oscillospira compared to immature individuals. 75 Similarly, the abundance of Oscillospira in male and female ASD rodent models exhibited substantial differences, and these differences may be due to sex specificity. 71 , 72 Xi et al found that the abundance of Oscillospira in the gut of specific-pathogen-free chickens decreased with increasing age.…”
Section: Factors Affecting the Abundance Of Oscillospiramentioning
confidence: 99%
“…Further research has shown that the diversity and composition of the gut microbiota affect the host’s health ( Marchesi et al, 2016 ), digestion ( Zhu et al, 2011 ; Flint et al, 2012 ), and behavior ( Hsiao et al, 2013 ), and that it may even be considered in other essential organs ( O’Hara and Shanahan, 2006 ). Many factors affect the composition and diversity of the gut microbiota, including diet ( Filippo et al, 2010 ; David et al, 2014 ; Merra et al, 2021 ; Wang et al, 2022 ), host characteristics ( Goodrich et al, 2014 ; Li et al, 2021 ), social contacts ( Sarkar et al, 2020 ), and environment ( Li et al, 2019 ; Wu et al, 2022 ). The diet is the most significant factor and even outweighs host genetics ( Hale et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the gut microbiota has been widely studied in invertebrates (Clark and Walker, 2018), amphibians (Bletz et al, 2016) and reptiles (Trevelline et al, 2019;Zhang et al, 2019Eliades et al, 2021, mammals (Hu et al, 2017;Song et al, 2017;Li et al, 2021), and birds (Ryu et al, 2012;Waite et al, 2012;Grond et al, 2018). In recent years, research into the gut microbiota in captive animals, such as Takydromus septentrionalis (Zhou et al, 2020), Neotoma albigula (Martínez-Mota et al, 2020), and Macaca mulatta (Chen et al, 2019) has also attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%